Urine pH and treatment outcomes in women with uncomplicated acute pyelonephritis - Hanchanachaikul, Tepnatee; Budkaew, Jiratha; Kulwedchakit, Warawut; Chumworathayi, Bandit (Asia-Pacific Journal of Science and Technology, 2024)
Urine alkalinisation is commonly used in some countries for treatment of the symptomatic uncomplicated UTI. However, there is lack of evidence to support their use for UTI and lack of evidence to support the association between urine pH and treatment outcomes. Therefore, in this study, authors aimed to investigate the associations between urine pH and 1) treatment outcomes, 2) clinical symptoms after treatment and 3) cure of disease within 48 hours. A retrospective-cohort study was done using Khon Kaen Hospital inpatient electronic database registration from 1st January 2014 to 31st December 2016. One hundred and eight women with first diagnosis of uncomplicated acute pyelonephritis were divided by the range of urine pH into quartiles (Q) (1st Q = urine pH < 5.50, 2nd Q = urine pH 5.50-6.00, 3rd Q = urine pH 6.01-7.00, 4th Q = urine pH 7.01-8.00). The associations between urine pH in each Qs and treatment outcomes, clinical symptoms, and cure within 48 h, were analyzed. There was an association between each quartile of urine pH before and after treatment (p= 0.024). After treatment, patients that changed their urine pH to higher quartiles were found in 19.6% more than to lower quartiles. Second and 3rd Qs before treatment were associated with clinical improvement of dysuria (p < 0.001, both) and suprapubic pain (p < 0.001, and p = 0.008, respectively). In conclusion, there was no association observed between each Qs of urine pH and cure of disease within 48 h, in women with uncomplicated acute pyelonephritis.